THEME OF TRANSPORT IN BASIC STRATEGIC DOCUMENTS OF REGIONS OF THE CZECH REPUBLIC (Perner's Contacts, 2011)
The article deals with a strategic planning of the regional development on the regional level of the Czech Republic with a focus on the theme of transport. The main aim of this paper is to explore and compare region’s approach to this issue based on information provided in the basic strategic documents. The results of the analysis show that the topic of transport occurs in all reviewed documents and that there can be observed both identical and different characteristics in the approaches of individual regions.
Keywords: regional development; transport; regions; Czech Republic; strategic planning